Design, production, and mechanical analysis of water-draining symmetrical sandals for slip prevention - Syamsul Hadi; Hangga Wicaksono; Muhammad Fakhruddin; Muhammad Nuhin; Muhammad Dafi Juniar Pradana; Aini Zuhra Binti Abdul Kadir; Muhd Ikmal Isyraf bin Mohd Maulana; Tuty Asma Abu Bakar (Politeknik Negeri Lhokseumawe, 2025)
Slipping accidents in ablution areas, sometimes leading to serious injuries or death, highlight the need for safer footwear. This study focuses on the design, production, and mechanical evaluation of symmetrical sandals with an elastic rubber-plastic composite base featuring horizontally branched drainage holes in the heel and phalange areas. The goal is to develop a sandal that effectively channels excess water away from the foot, minimizing slip hazards. The methodology includes symmetrical sandal design, mold fabrication, injection molding trials, and mechanical testing. The results indicate that the sandal base exhibits an elasticity range of 8 to 9.5 kg·s/mm, allowing effective water drainage. The tensile strength of the straps ranges from 17.1 to 20.8 kgf, surpassing the Indonesian National Standard (SNI 8879:2020) requirement of 12 kgf. These findings suggest that the sandal design enhances safety while maintaining durability.